Post-Postmodernist Fiction and the Rise of Digital Epitexts - Pignagnoli, Virginia (The Ohio State University Press, 2023)
Explores how digital epitexts surrounding contemporary novels by Michael Chabon, Jennifer Egan, Catherine Lacey, Meg Wolitzer, and Dave Eggers influence audience understanding and response.